IMPACT OF EARLY DIAGENESIS AND BULK PARTICLE GRAIN SIZE DISTRIBUTION ON ESTIMATES OF RELATIVE GEOMAGNETIC PALAEOINTENTISITY VARIATIONS IN SEDIMENTS FROM LAMA LAKE, NORTHERN CENTRAL SIBERIA - Nowaczyk N.R.; Harwart S.; Melles M. (My University, 2001)
High-resolution analyses of rock magnetic and sedimentological parameters were conducted on an 11m long sediment core from Lama Lake, Northern Siberia, which encompasses the late Pleistocene and the Holocene epochs. The results reveal a strong link between the median grain size of the magnetic particles, identified as magnetite, and the oxidation state of the sediment. Reducing conditions associated with a relative high total organic carbon (TOC) content of the sediment characterize the upper 7m of the core (~Holocene), and these have led to a partial dissolution of detrital magnetite grains, and a homogenization of grain-size-related rock magnetic parameters. The anoxic sediments are characterized by significantly larger median magnetic grain sizes, as indicated, for example, by lower median destructive fields of the natural remanent magnetization (MDFNRM) and lower ratios of saturation remanence to saturation magnetization (MSR/MS). Consequently, estimates of relative geomagnetic palaeointensity variations yielded large amplitude shifts associated with anoxic/oxic boundaries. Despite the partial reductive dissolution of magnetic particles within the anoxic section, and consequent minimal variations in magnetic concentration and grain size, palaeointensity estimates for this part of the core were still lithologically distorted by the effects of particle size (and subsidiary TOC) variations. Anomalously high values coincide with an interval of significantly more fine-grained sediment, which is also associated with a decrease in TOC content, which may thus imply a decreased level of magnetite dissolution in this interval. Calculation of relative palaeointensity estimates therefore seems to be compromised by a combined effect of shifts in the particle size distribution of the bulk sediment and by partial magnetite dissolution varying in association with the TOC content of the sediment.
Keywords: Holocene; Pleistocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Плейстоцен